Use of a competitive probe in assay design for genotyping of the UGT1A1*28 microsatellite polymorphism by the smart amplification process - Jun Watanabe; Yasumasa Mitani; Yuki Kawai; Takeshi Kikuchi; Yasushi Kogo; Atsuko Oguchi-Katayama; Hajime Kanamori; Kengo Usui; Masayoshi Itoh; Paul E. Cizdziel; Alexander Lezhava; Kenji Tatsumi; et al. (BioTechniques)
A key feature of the smart amplification process version 2 (SMAP-2) is the ability to suppress mismatch amplification by using a unique asymmetric primer design and Thermus aquaticus MutS (Taq MutS). However, we report here that use of SMAP-2 for polymorphism determination of the UGT1A1*28 allele required a further ancillary approach for complete background suppression. The UGT1A1*28 allele is a microsatellite copy number polymorphism. This is the first reported SMAP-2 assay designed for genotyping genetic variations of microsatellites. We found that by the addition of a primer to the amplification reaction, called a competitive probe (CP), assay specificity could be significantly enhanced. Including sample preparation time and use of a CP-enhanced SMAP-2 assay, we could rapidly detect the UGT1A1*28 polymorphism within 60 min. To test our method, we compared results from PCR sequencing and the CP-enhanced SMAP-2 assay on 116 human blood samples for UGT1A1*28 polymorphism and demonstrated perfect concordance. These results illustrate the versatility of SMAP-2 for molecular diagnostics and provide a new approach for enhancing SMAP-2 assay specificity.